Understanding the role of the gut ecosystem in diabetes mellitus. Issue 1 (24th May 2017) - Aw, Wanping; Fukuda, Shinji
Abstract: Diabetes mellitus is a type of metabolic disorder whereby patients are unable to regulate glycemia. It is currently a worldwide public health issue, and is a burden to society because of its disabling and common complications. Diabetes is multifactorial, and also induces the onset of other diseases. In the present report, we review the labyrinth encompassing the gut microbiota and gut microbiota‐derived metabolites in type 1 diabetes and type 2 diabetes pathogenesis. There have been exceptional improvements in deoxyribonucleic acid sequencing and mass spectrometry technologies throughout these past years, and these have allowed the comprehensive collection of information on our unique gut ecosystem. We would like to advocate incorporating metagenome and metabolome information for a comprehensive perspective of the complex interrelationships between the gut environment, host metabolism and diabetes pathogenesis. We hope that with this improved understanding we would be able to provide exciting novel therapeutic approaches to engineer an ideal gut ecosystem for optimal health. Abstract : Diabetes mellitus is a type of metabolic disorder whereby patients are unable to regulate glycemia. We will highlight the detailed relationships between gut microbiota and its metabolites on the pathogenesis of type 1 diabetes and type 2 diabetes. We hope that with this improved understanding using the following omics platforms: metagenomics, transcriptomics, metabolomics and proteomics, we would be able to provide exciting novel therapeutic approaches to engineer an ideal gut environment for optimal health.